Development and Validation of the Online Victimization Scale: Confirmatory Factor Analysis and Composite Reliability - Muzayyin, Muhammad Dzuhri; Al Afghani, Abdullah Azzam; Maula, Mela Minkhatul (Fakultas Psikologi UIN Syarif Hidayatullah Jakarta, 2025)
Online victimization is harmful actions directed at individuals or institutions through digital technology. This study aims to develop, validate, and examine the psychometric properties of the Online Victimization Scale (OVS). The researchers constructed and adapted several items from the Online Victimization Scale (OVS) by Tynes et al. (2014) and the Perceived Online Racism Scale (PORS) by Keum (2021), resulting in 54 items that were translated into Indonesian. A quantitative research method was employed using an accidental sampling technique. Data were collected from 204 individuals aged 14-23 years who were active social media users. Data analysis was conducted using Confirmatory Factor Analysis (CFA)to evaluate the factor structure. Score reliability was assessed by calculating composite omega and stratified alpha values using the lavaan package in R. The results indicated high inter-factor correlations, prompting a second-order factor analysis. The first-order and second-order models demonstrated good model fit indices with no significant differences, resulting in a final scale of 16 items. Measurement invariance testing using multi-group CFA confirmed that the scale met the criteria for scalar invariance, as indicated by minimal changes in ΔCFI and ΔTLI (<0.01). These findings validate the equivalence of the factor structure, factor loadings, and item intercepts between male and female participants, ensuring that score differences reflect actual differences in the online victimization construct rather than measurement bias.